Design, Simulation, and 3D Printing of a Lightweight Drone Frame for Farm Monitoring - BELLO, Abdulkareem; LUKMAN, Saleh S.; CHIZE, Tasie M.; ADEIZA, Yusuf O.; OKAFOR, Chibuzor A.; YAKUBU, Abdullahi O. (FUDMA Journal of Engineering and Technology, 2026)
This research presents the design, simulation, and fabrication by fused deposition modelling (FDM) 3D printing of a lightweight quadcopter frame for agricultural monitoring, aimed at developing a cost-effective and structurally efficient alternative to commercial drone frames. The project integrates Computer-Aided Design (CAD) in SolidWorks 2023 and Finite Element Analysis (FEA) in ANSYS Workbench 2024 to predict the frame's structural and thermal performance before fabrication. The drone frame geometry was reverse-engineered and scaled down from the DJI (Da-Jiang Innovations) Agras T100 platform, with adjustments to fit the mission requirements of low-altitude crop monitoring. Acrylonitrile Butadiene Styrene (ABS), of density 1.02 g/cm³ and tensile yield strength 40 MPa, was selected as the fabrication material due to its balance of strength, low density, and cost-effectiveness. Static, modal, steady-state thermal and thermal-stress simulations were carried out under a thrust load of 25 N per motor arm, a solar heat flux of 1000 W/m², an ambient temperature of 40 °C and a convective heat transfer coefficient of 20 W/m²K. The analysis returned a maximum equivalent (von Mises) stress of 2.4608 MPa and a maximum total deformation of 2.5538 mm, giving a factor of safety of 16.3 against the 40 MPa yield strength of ABS. The first five natural frequencies (41.67 Hz to 69.73 Hz) fell outside the propeller excitation band, confirming resonance avoidance. Steady-state thermal analysis returned a peak surface temperature of 51.021 °C, well below the 110 °C softening point of ABS, while combined thermal-mechanical loading raised the equivalent stress to only 12.456 MPa. The frame prototype was fabricated using the Creality CR-6 SE 3D printer, producing an assembled mass of 1.05 kg, which is 21% of the 5 kg maximum take-off weight, with dimensional deviation held within ±0.2 mm. Physical validation by static load and by drop tests from 0.25 m and 0.5 m (impact velocities of 2.215 m/s and 3.132 m/s) produced no cracking, layer separation or permanent deformation, supporting the simulation findings. Overall, the research demonstrates the feasibility of using low-cost 3D printing and polymer-based materials to produce functional UAV structures, offering significant reductions in manufacturing cost while maintaining mechanical reliability and operational safety.
Keywords: Drone frame, Precision agriculture, Finite Element Analysis (FEA), Computer-Aided Design (CAD), 3D printing, Quadcopter.